Flap Bebas Perforator Iliac Circumflex Superfisial (SCIP) untuk Rekonstruksi Ekstremitas Bawah pada Kasus Kanker: Laporan Kasus - Putra, Ade; Saratiana, Rasyiqah; Sofyan, Rian Fabian (Cermin Dunia Kedokteran, 2025)
Background: Synovial sarcoma, a rare tumor primarily afecting the lower extremities, often requires surgical excision to ensure tumor removal and limb preservation. This case highlights the importance of reconstructive options in achieving optimal functional and aesthetic outcomes for patients with large surgical defects. Case: A 51-year-old female with left foot synovial sarcoma (T2N0M0) underwent Chopart amputation to achieve clear surgical margins. The resulting defect was extensive, involving both skin and deeper soft tissues, making primary closure impossible. Reconstruction was performed using the Superfcial Circumfex Iliac Perforator (SCIP) free fap harvested from the groin region, which provided robust soft tissue coverage and minimized donor site morbidity. The patient’s postoperative course was uneventful, with no complications such as fap necrosis or infection. Early rehabilitation was initiated to restore limb function, and long-term follow-up showed no evidence of recurrence or functional impairment. Conclusion: Chopart amputation with SCIP fap is an efective option for foot synovial sarcoma management, ensuring both tumor clearance and limb function preservation.This case demonstrates the value of microsurgical reconstruction in complex oncologic cases and underscores the importance of multidisciplinary care in achieving favorable outcomes.